The future we chose : emerging perspectives on the centenary of the ANC - Ngcaweni, Busani; Dladla, Nonjabulo; Merrington, David; Pila, Berekile; Hirsch, Alan (Africa Institute of South Africa, 2013)
This book foregrounds emerging and different perspectives on the centenary of the ANC which was celebrated in February 2012. Differing in tenor, methodology and style, we present nineteen chapters that tackle various epochs and events in the making of the centenary of the oldest political organisation in Africa. The book offers new angles to our understanding of what sustained the ANC over one hundred years in spite of all the internal and external contradictions. --Cover.